(Z)-2-(5-Chloro-2-oxoindolin-3-ylidene)-N-methylhydrazinecarbothioamide - Qasem Ali, Amna (International Union of Crystallography, 2012)
In the title compound, C(10)H(9)ClN(4)OS, an intramolecular N—H⋯O hydrogen-bonding interaction and an N—H⋯N interaction generate ring motifs [graph sets S(6) and S(5), respectively]. In the crystal, molecules form a chain through N—H⋯O hydrogen bonds, and these are extended by N—H⋯S hydrogen-bonding interactions into an infinite three-dimensional network. The crystal structure also exhibits weak C—H⋯π interactions.